PENGARUH PENERAPAN LAPORAN ARUS KAS OPERASI, ECONOMIC VALUE ADDED, DAN LABA KOTOR TERHADAP VOLUME PERDAGANGAN SAHAM PERUSAHAAN PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Muhammad Ghozi Falih Afifi Falih; Alwan Sri Kustono; Gardina Aulin Nuha (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to examine the effect of cash flow, economic value added and gross profit on stock volume by trading stock trading volume. In this study, all plantation companies listed on the Indonesia Stock Exchange for the period 2016-2019 using SPSS Version 21 program. The results showed that cash flow had no significant effect on stock volume. Economy value added and gross profit have no effect on stock volume. Share volume cannot mediate or be an intervening variable between total cash flow, economic value added and gross profit to share volume.